Remote sensing in humanitarian logistics: An integrative approach - Christian Hein; Henning Hünemohr; Rainer Lasch (The Road to a Digitalized Supply Chain Management: Smart and Digital Solutions for Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 25, 2018)
Remote sensing is becoming increasingly important for the acquisition of information in humanitarian logistics. While different platforms (e.g. satellites, drones) with their own characteristics and advantages exist, the literature often refers to just one of them. This paper aims at integrating platforms, making full use of their specific advantages. The work is conceptual, comparing different remote sensing platforms according to their advantages and limitations as well as evaluating the potentials of their combination drawing on both academic and practitioner literature. Moreover, drone test flights (hexacopter) demonstrate the practical implementation of data acquisition, processing, as well as their integration. The results show that the combination of data gathered via different remote sensing platforms is highly beneficial for the management of humanitarian logistics in terms of quality, time, flexibility, and cost. Furthermore, the feasibility has been demonstrated by the drone experiment and the respective data processing and integration. To the best of our knowledge, this is the first work systematically examining the integration of data acquired via different remote sensing platforms considering their specific advantages and the area of application in the context of humanitarian logistics as well as demonstrating the feasibility through the use of an experimental drone flight. The results discussed represent the first step in the use of combined remote sensing data in humanitarian logistics; specific applications should be examined more in detail. Furthermore, challenges in the use of such data have to be overcome, such as their integration into the information management processes of humanitarian actors.
urn:nbn:de:gbv:830-88223327; 10419/209194; https://econpapers.repec.org/RePEc:zbw:hiclpr:25
Keywords: 650; Humanitarian Logistics; Humanitarian Operations; Remote Sensing; Drones